Predicting Pharmacokinetic Profiles of Sunflowerâ€™s (Helianthus annuus L.) Active Compounds using in Silico Approach - Firdausy, Alif Firman; Muti'ah, Roihatul; Rahmawati, Eka Kartini (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Introduction: Sunflower (Heliantus annuus L.) widely known as medicinal plant for treating several diseases, such as hypertension, allergy, pain, inflammation, and cancer. It contains various bioactive compounds which some of them were hellianuols. Hellianuols are a sesquiterpene lactones which marked by benzene fused 6- to 8-membered cyclic ether ring structure. To make sure that hellianuols were adequate for development as a new chemical entities, we predicted some pharmacokinetic parameters of several hellianuols compounds (A to L) through in silico approach.Methods: We constructed 3 dimensional structures of hellianuol A, B, C, D, E, F, G, H, I, J, K and L then generated the SMILE codes of each compound. These codes then used as main material for running pkCSM online tool to predict absorption, distribution, metabolism, and excretion profile of each compounds.Results: Helianuols predicted to be well absorbed in intestine (90,793% to 95,384% permeability), skin (Log Kp: -2,662 to -3,570), and high permeability against monolayer Caco-2 cell lines (LogPapp: 1,186 to 1,341 Ã—10-6cm/s). Unfortunately, it had been predicted that hellianuols does not well distributed in the body based on volume of distribution at steady state (VDSS: 0,094 to 0,317) value. But its also predicted that most of hellianuols had a capability to pass through blood-brain barriers (LogBBB: up to 0,389) and penetrated into central nervous system as well. Only hellianuol G, H and K predicted to be metabolized by CYP1A2 inhibitor and only hellianuol A, B, D, E and K metabolized by CYP2C19. Also predicted that hellianuols were excreted in around 0,719 to 1,082 mg/kg/day.Conclusion: Hellianuols contained in leaf aqueous extract of sunflower predicted to be a good new pharmaceutical entities candidate based on its pharmacokinetic profiles.Keywords: Hellianuol, sunflower, pharmacokinetic profie, pkCSM online tool